Students’ Perception: The Use of Cell Phones to Enhance Understanding in the English Classroom - Jelita, Dwi Mutiara; Rakhmawati; Fauziana, Erni (ICONELT, 2024)
EFL teachers might face challenges in teaching English language skills to students from different proficiency, and employ the new strategies to learn English effectively. Using technological tools, such as cell phones in the classroom, can enhance student engagement and provide access to rich information during the learning process. This study aims to investigate the students’ perception in eighth grade at one of the junior high schools in Surabaya about the use of cell phones in the English classroom to enhance their understanding. For this study, the researcher used a quantitative descriptive, using a close-ended questionnaire. The result from the questionnaire showed that most of the students agreed that cell phones had a positive impact on enhancing their understanding. They felt fun because they could play while learning and provide many applications that can be used to practice English.